Elevating Food Perceptions Through Luxury Verbal Cues: An Eye-Tracking and Electrodermal Activity Experiment. Issue 1 (February 2023) - Sung, Billy; Butcher, Luke; Easton, Julia
Many brands, including food brands, draw on connotations of luxury to elevate the favorability of consumer perceptions. This is often undertaken using cues in marketing communications; however, no research has examined the psychophysiological effect of luxury cues on consumer attention. Evidently, this study is the first experiment to use eye-tracking and skin conductance analysis to investigate how luxury cues in marketing communications can influence consumer perceptions of a food product. Our findings demonstrate that the use of luxury verbal cues can significantly enhance the attention to hedonic processing and elevate food brand perceptions. Specifically, consumers pay greater attention to the imagery of marketing communications when exposed to luxury verbal cues, which, in turn, enhance arousal and positive brand evaluations. Our research provides valuable theoretical and managerial implications for food brands using communications such as content marketing and advertising to build favorable brand connotations and elevate brand positioning.